Effectiveness of a structured educational intervention using psychological delivery methods in children and adolescents with poorly controlled type 1 diabetes: a cluster-randomized controlled trial of the CASCADE intervention. Issue 1 (1st June 2016) - Christie, Deborah; Thompson, Rebecca; Sawtell, Mary; Allen, Elizabeth; Cairns, John; Smith, Felicity; Jamieson, Elizabeth; Hargreaves, Katrina; Ingold, Anne; Brooks, Lucy; Wiggins, Meg; Oliver, Sandy; et al.
Abstract : Introduction: Type 1 diabetes (T1D) in children and adolescents is increasing worldwide with a particular increase in children <5 years. Fewer than 1 in 6 children and adolescents achieve recommended glycated hemoglobin (HbA1c) values. Methods: A pragmatic, cluster-randomized controlled trial assessed the efficacy of a clinic-based structured educational group incorporating psychological approaches to improve long-term glycemic control, quality of life and psychosocial functioning in children and adolescents with T1D. 28 pediatric diabetes services were randomized to deliver the intervention or standard care. 362 children (8–16 years) with HbA1c≥8.5% were recruited. Outcomes were HbA1c at 12 and 24 months, hypoglycemia, admissions, self-management skills, intervention compliance, emotional and behavioral adjustment, and quality of life. A process evaluation collected data from key stakeholder groups in order to evaluate the feasibility of delivering the intervention. Results: 298/362 patients (82.3%) provided HbA1c at 12 months and 284/362 (78.5%) at 24 months. The intervention did not improve HbA1c at 12 months (intervention effect 0.11, 95% CI −0.28 to 0.50, p=0.584), or 24 months (intervention effect 0.03, 95% CI −0.36 to 0.41, p=0.891). There were no significant changes in remaining outcomes. 96/180 (53%) families in the intervention arm attended at least 1 module. The number of modules attended did not affect outcome. Reasons for low uptake included difficulties organizing groups and work and school commitments. Those with highest HbA1cs were less likely to attend. Mean cost of the intervention was £683 per child. Conclusions: Significant challenges in the delivery of a structured education intervention using psychological techniques to enhance engagement and behavior change delivered by diabetes nurses and dietitians in routine clinical practice were found. The intervention did not improve HbA1c in children and adolescents with poor control. Trial registration number: ISRCTN52537669, results.